Keragaman Pertumbuhan Bibit Meranti Sarang Punai (Shorea parvifolia dyer.) Populasi Muara Wahau, Kalimantan Timur - Mashudi - Mashudi (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
Shorea parvifolia is a member of Dipterocarpaceae its prospective for plantation forest development. The wood can be used for industrial raw materials of veneer, plywood, bulkhead boards, home furnishings, frames, wooden ornaments and moldings. High productivity of S. parvifolia forest plantation should be supported by continuous quality seeds. Generative seed procurement still faces obstacles because the fruit season does not take place every year and the seeds are recalcitrant. An alternative that can be done is the procurement of seeds of S. parvifolia vegetatively through shoot cuttings technique. Starting from that hence this research is done with purpose to know influence of mother tree to diversity growth of S. parvifolia seedling as material of shoot cuttings. The experimental design used in this study was Complete Randomized Design (CRD) with 20 mother trees consisting of 10 seeds. The results showed that the mother tree significantly affected the growth of height and stem diameter and no significant effect on the robustness of S. parvifolia seedlings at 8 months of age. Height growth is divided into three groups with the best group occupied by 17 mother trees in the range of 33.9 - 45.2 cm. The growth of stem diameter was divided into four groups with the best group occupied by 17 parent trees in the range of 3.59 - 4.75 mm. The correlation between height and